Waqf Utilization Strategies in Improving the Economic Welfare of the Muslim Community - Nurachmadi, Senki; Riyanto, Sugeng; Mutaufiq, Ali (International Journal of Sharia Business Management, 2024)
This study aims to analyze the strategy of utilizing waqf as an instrument to improve the economic welfare of Muslims. Waqf, as a form of Islamic philanthropy, has great potential in overcoming the problems of poverty and inequality if managed properly. The research method used is a qualitative approach with data collection techniques in the form of literature studies, in-depth interviews, and policy analysis related to waqf in several Muslim-majority countries. The results of the study indicate that modern, transparent, and professional waqf management can make a significant contribution to the economic welfare of the community. Important factors that support the success of this waqf are the existence of a clear regulatory framework, public awareness, and collaboration between the government, waqf institutions, and the private sector. The conclusion of this study is that optimizing waqf management with an integrated and innovative strategy has great potential to improve the economic welfare of Muslims. Implementation of an effective strategy requires synergy between various stakeholders, strengthening regulations, and utilizing modern technology to ensure the sustainability and efficiency of waqf management